2018
DOI: 10.1167/iovs.17-23451
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Decentration and Induced Corneal Higher-Order Aberrations Following Small-Incision Lenticule Extraction Procedure

Abstract: Citation: Lee H, Roberts CJ, ArbaMosquera S, Kang DSY, Reinstein DZ, Kim T. Relationship between decentration and induced corneal higherorder aberrations following small-incision lenticule extraction procedure. Invest Ophthalmol Vis Sci. 2018;59:2316-2324. https://doi.org/ 10.1167/iovs.17-23451 PURPOSE. To investigate the amount of lenticule decentration following small-incision lenticule extraction (SMILE) by using the Keratron Scout tangential topography difference map, and the relationship between the magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 36 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…Four kinds of aberrations were analyzed because of their clinical importance: spherical aberration (SA), vertical coma, horizontal coma, and total HOAs. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Four kinds of aberrations were analyzed because of their clinical importance: spherical aberration (SA), vertical coma, horizontal coma, and total HOAs. 14 …”
Section: Methodsmentioning
confidence: 99%
“…The normal corneal vertex could be measured by corneal topography machines, with a Scheimpflug camera and/or a Placido system. 9,10 Corneal vertex, a stable reference of the cornea, has been recommended to be the central point of alignment for laser corneal refractive surgeries, because it has been proven to be closest to the corneal intercept of the visual axis. 7,1113…”
Section: Main Centration Axes In Corneal Refractive Surgerymentioning
confidence: 99%
“…12 It is noteworthy that vertical decentration was observed more common among the lenticule decentrations, and postoperative induced HOAs, including vertical coma and spherical aberration occurred more frequently among the surgeons at their early learning stage. 10,11,17,18…”
Section: Main Centration Axes In Corneal Refractive Surgerymentioning
confidence: 99%
“…Accurate centration is crucial in refractive surgery because decentered treatment may result in undesirable visual outcomes. 5 Previous studies have shown that CV is an ideal ablation center with fewer postoperative higher-order aberrations (HOAs) introduced than PC. 6 , 7 With the increase in HOAs, there are a series of complications related to postoperative visual qualities, such as poor night vision, glare, monocular diplopia, and astigmatism.…”
Section: Introductionmentioning
confidence: 99%